2002
DOI: 10.2331/fishsci.68.sup1_226
|View full text |Cite
|
Sign up to set email alerts
|

Stock fluctuations of the Japanese common squid, <i>Todarodes pacificus</i>, related to recent climate changes

Abstract: SUMMARY: In Todarodes pacificus, recruitment success is most likely dependent on the physical and biological environments of the spawning and nursery grounds. Annual catches of T. pacificus in Japanese and Korean waters have markedly increased since the late 1980s and the recent catch is equal to that of the 1960s. Here re proposed is a possible scenario for the stock increase since the late-1980s based on GIS analysis of changes in the inferred spawning area during 1984-1999. This study suggests that winter-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 1 publication
1
17
0
3
Order By: Relevance
“…During cool water regimes (e.g. after the 1977 regime shift) the winter spawning areas of common squid contracted and were restricted to the East China Sea (Sakurai et al 2000;Sakurai et al 2002). Conversely, during warm water regimes (e.g.…”
Section: Koreamentioning
confidence: 97%
“…During cool water regimes (e.g. after the 1977 regime shift) the winter spawning areas of common squid contracted and were restricted to the East China Sea (Sakurai et al 2000;Sakurai et al 2002). Conversely, during warm water regimes (e.g.…”
Section: Koreamentioning
confidence: 97%
“…추계군과 동계군이 대다수를 차지하며 그 중에서도 동계군의 자원량이 가장 많은 것으로 (Murata, 1989;Kawabata et al, 2006) 알려져 있다. Sakurai et al(2002) (Murata, 1978), Kim(1990) (Kim and Kang, 1998). 부산주변해역에서 채집된 살오징어는 외투장의 크기에 따라 먹이 생물의 조성이 다르고, 계 절에 따라서는 산란기에 관계없이 연중 섭이하였다 (Song et al, 2006).…”
Section: 서 론unclassified
“…These regimes coincided with variation in common squid catches, particularly the declines in the early 1980s catch, and the increases in the late 1980s. Sakurai et al (2000Sakurai et al ( , 2002 suggested that the winter spawning areas for common squid in the East China Sea shrank when the adult stocks decreased during the cool regime. Fall and winter spawning areas expanded and overlapped in the Sea of Japan and East China Sea when adult stocks increased during the warm regime that occurred after 1989.…”
Section: Mackerel Including Chub (S Japonicus) and Spotted Mackerelmentioning
confidence: 99%